Synthesis, Identification and Antimicrobial Activity of 2-Phenyl-3-(Ethyl Acetate)-Quinazolin-4(3h)-One Nucleus Linked with Pyrazole, Pyrazolinone and Pyrimidine Ring - Majidi, Suaad M. H. Al-; Sahib, Maryam M. (International Journal of Psychosocial Rehabilitation, 2020)
–A new series of pyrazole, pyrazolinone and pyrimidine derivatives were synthesized from quinazolin-4(3H)-one nucleus and then their actions as antimicrobial agents estimated in present work. Quinazolinone skeleton as starting compound was designed in three steps. The first step including formation of 2-benzamidobenzoic acid [1] by reaction of anthranilic acid with benzoyl chloride. The second step produced 2-phenyl-4H-benzo[3,1]oxazin-4-one [2] from cyclized of compound [1] by acetic anhydride. The third step involved gave 2-phenyl-3-(ethyl acetate)-quinazolin-4(3H)-one [3] by treatment of compound [2] with ethyl glycinate. Compound [3] was reacted with paraphenylenediamine to give 2-phenyl-3-(acetamido-4-aminophenyl)-quinazolin-4(3H)-one [4]. The diazotization of compound [4] with sodium nitrate and concentration HCl at 0-5 oC form diazonium salt that coupled with active methylene compounds such as acetyl acetone and ethyl aceto acetate to afforded corresponding compounds [5] and [6]. Hydrazono acetyl acetone [5] and hydrazono ethyl aceto acetate [6] treatment with hydrazine and substituted hydrazine to yielded series of pyrazole derivatives [7-11] and pyrazolinone derivatives [12-16] respectively. pyrimidine derivatives [17-18] prepared via cyclization of hydrazono acetyl acetone [5] with urea and thiourea. The newly synthesized compounds elucidate their structure by different spectral techniques involved FTIR, 1H-NMR and 13C-NMR. Some of its physical properties were measured. Furthermore we have evaluated the activity of some prepared compounds against different types of bacteria and fungi strain. The result showed significant effects for these compounds on microorganisms.